2001
DOI: 10.1126/science.1064829
|View full text |Cite
|
Sign up to set email alerts
|

Taking Cell-Matrix Adhesions to the Third Dimension

Abstract: Adhesions between fibroblastic cells and extracellular matrix have been studied extensively in vitro, but little is known about their in vivo counterparts. Here, we characterized the composition and function of adhesions in three-dimensional (3D) matrices derived from tissues or cell culture. "3D-matrix adhesions" differ from focal and fibrillar adhesions characterized on 2D substrates in their content of alpha5beta1 and alphavbeta3 integrins, paxillin, other cytoskeletal components, and tyrosine phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

99
2,388
3
22

Year Published

2002
2002
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 2,737 publications
(2,512 citation statements)
references
References 23 publications
99
2,388
3
22
Order By: Relevance
“…3). A previous study by other group demonstrated that ERK activation is independent from the FAK-regulated pathway in fibroblasts cultured in cell-derived 3-D matrix [30]. These results strongly suggest that paxillin may function as a (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…3). A previous study by other group demonstrated that ERK activation is independent from the FAK-regulated pathway in fibroblasts cultured in cell-derived 3-D matrix [30]. These results strongly suggest that paxillin may function as a (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…In a 3D microenvironment, cells need to either degrade the extracellular matrix (ECM) or squeeze through small pores in amoeboid fashion (Wolf and Friedl 2008), and they may experience chemokine gradients differently, since many are matrix-binding (Patel et al 2001). As a result, cells behave very differently in 3D vs. 2D environments (Behnsen et al 2007;Cukierman et al 2001;Griffith and Swartz 2006;Pedersen and Swartz 2005). Thus, to examine cell migration in a physiologically realistic setting, migration assays need to accurately recapitulate the 3D microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the ECM influences the development, shape, migration, proliferation, survival, and function of the fibroblasts. The fibroblast belongs to the group of adherent cells, and attaches to the ECM by integrins (Cukierman et al, 2001;Jiang and Grinnell, 2005). The mobility of the fibroblast and its ability to contract the ECM are important properties in the maintenance of the ECM (Barocas et al, 1995;Dembo and Wang, 1999;Eastwood et al, 1998;Friedl and Bröcker, 2000;Friedrichs et al, 2007;Grinnell, 2003;Lo et al, 2000;Poole et al, 2005).…”
mentioning
confidence: 99%